Genetic Tools to Study Cardiovascular Biology - Garcia-Gonzalez, Irene; Mühleder, Severin; Fernández-Chacón, Macarena; Benedito, Rui (Frontiers in Physiology, 2020)
Progress in biomedical science is tightly associated with the improvement of methods and genetic tools to manipulate and analyse gene function in mice, the most widely used model organism in biomedical research. The joint effort of numerous individual laboratories and consortiums have contributed to the creation of a large genetic resource that enables scientists to image cells, probe signaling pathways activities or modify a gene function in any desired cell type or time point, à la carte. However, as these tools significantly increase in number and become more sophisticated, it is more difficult to keep track of each tool possibilities and understand their advantages and disadvantages. Knowing the best currently available genetic technology to answer a particular biological question is key to reach a higher standard in biomedical research. In this review we list and discuss the main advantages and disadvantages of available mammalian genetic technology to analyze cardiovascular cell biology at higher cellular and molecular resolution. We start with the most simple and classical genetic approaches and end with the most advanced technology available to fluorescently label cells, conditionally target their genes, image their clonal expansion and decode their lineages.